Functional differential equations with nonlocal initial conditions. (1997) - Aizicovici, Sergiu; Gao, Yun
Abstract : We study the existence, uniqueness, asymptotic properties, and continuous dependence upon data of solutions to a class of abstract nonlocal Cauchy problems. The approach we use is based on the theory of m -accretive operators and related evolution equations in Banach spaces.